PENGARUH KADAR LUMPUR PADA AGREGAT HALUS DALAM MUTU BETON - Purwanto Purwanto; Yulita Arni Priastiwi (TEKNIK, 2012)
Clay lumps on the aggregate levels is one of the factors that may cause disruption of the binding process andhardening of concrete. Clay lump can not blend with cement so that blocking a merger between the cement withaggregates which eventually led to the compressive strength of concrete will be reduced in the absence ofbinding to each other. SK SNI S-04-1989-F, the allowable levels of clay lump maximum of 5% to fine aggregate(sand) and maximum of 1% for coarse aggregate (split).In this study to determine the effect of the clay lump on the fine aggregate content on compressive strength ofconcrete on five (5) variations levels of the category of clean clay lump with content of 1% and 2%, medium claylump 4% and dirty sand with levels 7 % and 11%, whereas for the coarse aggregate clay lump content was0.7%.From the results of a study of 90 cylindrical specimens showed that the small amount of clay lump, the higherthe compressive strength of concrete. Concrete compressive strength test results on average with dirty clay lumpcontent was 31.30 MPa, compressive strength for the concrete medium with clay lump levels were at 33.92 MPaand compressive strength for the concrete clean of clay lump 36.68 MPa. Compared to the dirty clay lump anincrease in the levels of average compressive strength for moderate levels of 8,37% and the clean sand of17,19%. Besides affecting in compressive strength, clay lump levels also affect the weight of concrete, andconcrete density. The greater the level of clay lump, weight of concrete and concrete density will be lower.Compared to the dirty clay lump an increase in the levels of average concrete density for moderate levels of 6,54% and the clean sand of 12,59%.